(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
In the light of the globalization Which surrounds the business environment and whose impact has been reflected on industrial economic units the whole world has become a single market that affects its variables on all units and is affected by the economic contribution of each economic unit as much as its share. The problem of this research is that the use of Pareto analysis enables industrial economic units to diagnose the risks surrounding them , so the main objective of the research was to classify risks into both internal and external types and identify any risks that require more attention. The research was based on the hypothesis that Pareto analysis used, risks can be identified and addressed before they occur. The most important conclusions were the absence of the elements of innovation and design, which are the basis of the composition of the value and gain customer satisfaction as the shape of the packaging 2-liter light remained the same since the production in this manner. The research concluded by focusing on quality and using one of its tools to solve the problems that result from deviation in quality and thus avoid the loss that the company is subjected to as a result of this deviation.